Comparative biomechanical analysis between hammer throwers of different performance levels - Gutierrez-Davila, M.; Rojas Ruiz, F. J. (Journal of Human Movement Studies, 2005)
The aim of the present study was to carry out an exploration and biomechanical analysis of the most significant factors in the theoretical model of the hammer throw in throwers with different performance levels. The purpose of this biomechanical analysis was to show both the differences in the biomechanical factors between each group of throwers, as well as the variations within each group. Thirty hammer throwers were analysed during the course of five national and international competitions. On the basis of the distance reached, three groups of ten throwers were selected: a) National group (between 52-62m length) b) Elite National group (between 63-74m) and c) Elite International group (between 76-81 m). The methodology proposed by Dapena (1984) and Gutierrez et al (2002) of three-dimensional (3D) photogrammetric techniques was used for the analysis. The results revealed clear significant differences between groups (p<.001) in the time employed for each turn, the Elite International group taking the least time. Clear differences between groups were found in the thrower's mass (p<.001), with the average of the Elite International group being the heaviest, and there were certain differences between groups in the angle of torsion of the trunk in the final turn (p<.01), with the lowest average in the Elite International group. No statistically significant differences among the groups were found in the other variables selected: the thrower's height, the angular displacement of the hammer in the double support phase and the average radius of turn of the hammer head, during the single and double phases in each turn.